Исследование по определению микроколичеств мышьяка методом ППН - Каплин А. А. Анатолий Александрович; Вейц Н. А.; Стромберг А. Г. Армин Генрихович; Трушина Л. Ф. (1976, 1976)
Заглавие с титульного листа